Hydrogen – a truly sustainable transport fuel?. Issue 3 (1st April 2003) - Hart, David
Abstract : Transport energy, particularly that derived from fossil fuels, is causing increasing problems worldwide. Hydrogen as a transport fuel offers solutions to many of these issues. Produced from renewable resources, hydrogen could cut greenhouse gas emissions to zero, and the use of some fossil sources could even reduce emissions. Air quality and noise problems would also be addressed. Although developments are underway, and many countries see hydrogen as part of a sustainable energy future, implementation is being hindered by social and economic considerations and immature technology. To ensure that expectations are met, support is needed from policy makers, industry, and the public.